THE UTILIZATION OF TUNA BONE FLOUR (Thunnus sp) ON THE QUALITY OF ARAI CHIPS - Sulistia, Yosi; Sari, Ira; Iriani, Dian (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACT            This research aims to determine the effect of adding tuna bone flour to the quality of arai chips and to determine the quality content of organoleptic, proximate, and calcium in arai chips. The treatments given consisted of (T0) without 0% bone flour, (T1) giving 5% of tuna bone flour, (T2) giving 10% of tuna bone flour, and (T3) giving 15% of tuna bone flour. The analysis parameters observed were the organoleptic quality test (appearance, aroma, taste, and texture), proximate test, and calcium test. The addition of tuna bone flour 5% (25 g) (T2) resulted in the best arai chips with a characteristic color value of 7.91 (slightly brownish yellow), aroma 7.77 (slightly have kind of bone flour aroma), taste 7.85 (a little bone flour taste), and texture 7.96 (crispy) with moisture, ash, protein, fat, carbohydrate (by difference), and calcium content was 3.39%, 6.81%, 5.52%, 42.12%, 45.55% and 1.11%, respectively.Keywords: arai chips, quality acceptance, tuna bone flour